Case Report: Atrial fibrillation as the initial presentation of an adult anomalous origin of the left coronary artery from the pulmonary artery - Cai He; Jun Ma; Wei Wang (Frontiers in Cardiovascular Medicine, 2026)
Anomalous origin of the left coronary artery from the pulmonary artery (ALCAPA) is a rare congenital coronary anomaly characterized by diverse clinical presentations. Atrial fibrillation (AF) as the initial presentation is exceptionally rare and often results in misdiagnosis. This report describes a rare case of adult-type ALCAPA manifesting initially as AF, detailing a comprehensive surgical strategy and long-term outcomes.